1997
DOI: 10.1002/(sici)1098-2396(199710)27:2<122::aid-syn3>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate decarboxylase (GAD67 and GAD65) gene expression is increased in a subpopulation of neurons in the putamen of parkinsonian monkeys

Abstract: The cellular distribution of the mRNAs encoding for the two isoforms of glutamate decarboxylase, GAD67 and GAD65, was analyzed by in situ hybridization histochemistry in the caudate nucleus and putamen of control and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated parkinsonian squirrel monkeys. On brain sections processed with a radioactive and a digoxigenin-labeled cRNA probe, the GAD67 and GAD65 mRNAs were colocalized in virtually all labeled neurons of the caudate nucleus and putamen, in both co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…This was not expected. Anatomical studies of 6-OHDAlesioned rats revealed that striatal expression of GAD (glutamate decarboxylase), the synthetic enzyme for GABA, rises (Soghomonian and Laprade, 1997). Moreover, the terminals of striatopallidal D 2 MSNs in the GPe and the striatum are enlarged, in parallel with an increased expression of the releasable peptide enkephalin (Ingham et al, 1991(Ingham et al, , 1997.…”
Section: Collateral Inhibition Is Attenuated In Pd Modelssupporting
confidence: 67%
“…This was not expected. Anatomical studies of 6-OHDAlesioned rats revealed that striatal expression of GAD (glutamate decarboxylase), the synthetic enzyme for GABA, rises (Soghomonian and Laprade, 1997). Moreover, the terminals of striatopallidal D 2 MSNs in the GPe and the striatum are enlarged, in parallel with an increased expression of the releasable peptide enkephalin (Ingham et al, 1991(Ingham et al, , 1997.…”
Section: Collateral Inhibition Is Attenuated In Pd Modelssupporting
confidence: 67%
“…The extent to which GABA neurotransmission is upregulated in the indirect striatopallidal circuit in chronic symptomatic parkinsonian monkeys is unknown. However, GAD65 and GAD67 mRNA levels were increased in the dorsolateral putamen in acute parkinsonian monkeys (Soghomonian and Laprade, 1997). In these animals, GAD mRNA levels were increased in PPE-labeled (presumably striatopallidal) neurons but not in PPE-unlabeled neurons.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, based on electrophysiological and microdialysis findings, the activity of GPe neurons and, thus, of the GPe-GPi projection is reduced in parkinsonism. Based on measurements of striatal GAD mRNA levels, it is also known that striatal neurons projecting to GPi are not overactive in MPTP-treated monkeys (Soghomonian and Laprade, 1997). It is therefore most likely that the increased level of GAD protein in GPi represents increased activity of local axon collaterals of GPi neurons and is therefore another indicator that GPi activity is enhanced in MPTP-treated animals.…”
Section: Global Neuronal Activity Changes In Parkinsonismmentioning
confidence: 99%